Community knowledge, attitudes and behaviors in prevention of COVID-19 transmission: A systematic review - Kholis Ernawati; Istri Bela Cantika; Riska Rammadita Isaputri; Atika Wahyu Andari; Muhammad Fajar Ramadhan; Shifa Khaunan Nathasia; Rifqatussa’adah Rifqatussa’adah; Hayati Sari Hasibuan; Lina Tri Mugi Astuti; Yunita Ismail (Intelektual Pustaka Media Utama, 2021)
The research objective was to determine the community's knowledge, attitudes, and behavior in preventing the transmission of COVID-19 with a systematic review approach. The research method used the protocol preferred reporting items for systematic review and meta-analysis (PRISMA). The research variables were sociodemographic, knowledge, attitudes, and behaviors to prevent COVID 19. The search process for articles was accessed on three electronic journal databases. The article inclusion criteria are quantitative research, primary data, and year of publication (January-July 2020), in English, open access; have gone through the peer review stage, and full-text articles. A descriptive analysis was carried out on each research variable. The results showed ten articles that fit the inclusion criteria, consisting of 100% sociodemographic variables, 90% knowledge, 90% attitude, and 80% behavior. The number of articles with significant research results on knowledge variables (covering aspects of disease recognition, modes of transmission, general symptoms, and methods of prevention) was 61.11% of articles. The number of significant articles on attitude variables (including self-isolation, use of masks, social distancing, COVID-19, and government) was 35.54%. The number of substantial articles on the variable of preventive behavior (including handwashing, social distancing, hand sanitizers, use of masks, and self-isolation) was 45%.